2010
DOI: 10.1021/jp102525y
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of 3D-Ordered Macroporous Nanocrystalline Iron Oxide Films with Highly Efficient Visible Light Induced Photocatalytic Activity

Abstract: A facile approach of layer-by-layer depositing and hydrolysis of FeCl3 is developed to fabricate 3D-ordered Fe2O3 film. The 3D-ordered Fe2O3 film was characterized by SEM, XRD, and DRUV−vis. It has 3D-ordered interconnecting macropores (340 nm) with nanocrystalline hematite Fe2O3 walls (27.2 nm). The 3D-ordered macroporous nanocrystalline Fe2O3 film exhibits 2.4 times larger photocatalytic activity for the photodegradation of dye in the presence of H2O2 under visible irradiation than the nanocrystalline α-Fe2O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 44 publications
4
67
0
Order By: Relevance
“…SnO 2 and α -Fe 2 O 3 , both important functional materials, have been intensively investigated separately for their applications as photocatalysts, [ 15 ] gas sensors, [ 16 ] and electrodes. [ 17 ] It has been previously demonstrated that a SnO 2 / α -Fe 2 O 3 hybrid composite can yield enhanced functions like gas sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…SnO 2 and α -Fe 2 O 3 , both important functional materials, have been intensively investigated separately for their applications as photocatalysts, [ 15 ] gas sensors, [ 16 ] and electrodes. [ 17 ] It has been previously demonstrated that a SnO 2 / α -Fe 2 O 3 hybrid composite can yield enhanced functions like gas sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the red-edge of stop-band for inverse opals is thought to be more important in photocatalysis because of the relative higher refractive index of skeletal material. In the present work, because of the varied incident angle in the range of 0-90°, the stop-bands of these 3DOM-SrTiO3 materials were variable in a wide range [68,69] . It would result in a wide slow photon region at the red-edges of stop-band, and this slow photon region was partially overlapped with its stop-band.…”
Section: The Slow Photon Effect On the Efficiency Of Photocatalytic Hmentioning
confidence: 66%
“…Broadband excitation should be avoided to allow one to discriminate between photogenerated carriers originating from slow photons and those originating from normal bandgap excitation. Under these controlled experimental conditions, one can quantify the level of photocatalytic enhancement attributed to the slow photon effect and utilize the ground rules established in the seminal work by Chen et al [20][21][22] and others 19,26 to engineer the stop band position for maximum photocatalytic activity.…”
Section: Tuning the Photonic Crystal Stop Band Around Sensitizer Excimentioning
confidence: 99%